Biomechanical characterization of vertebral body replacement in situ: Effects of different fixation strategies. (December 2020) - Dong, Enchun; Shi, Lei; Kang, Jianfeng; Li, Dichen; Liu, Bin; Guo, Zheng; Wang, Ling; Li, Xiangdong
Highlights: The biomechanical performance of the reconstructed lumbar spine system with lateral or posterior fixation strategy was evaluated and compared using finite element method. The Pros and Cons in terms of the strength and long-term stability of lateral and posterior fixation strategies was thoroughly discussed, so did the associated clinical issues. It is suggested that the stability and functional restoration, including load-sharing and functional motion restoration, of the reconstructed spinal system should be balanced during designing. Abstract: Background and Objective: Artificial vertebral implant with a lateral or posterior screw-rod fixation system are usually employed in lumbar reconstruction surgery to rebuild the lumbar spine after partial resection due to a tumor or trauma. However, few studies have investigated the effect of the various fixation systems on the biomechanics of the reconstructed lumbar system. This study aims to evaluate the influence of different surgical fixation strategies on the biomechanical performance of a reconstructed lumbar spine system in terms of the strength and long-term stability. Methods: Two typical lumbar spine reconstruction case models that correspond to lateral or posterior fixation systems were built based on the clinical data. Finite element analyses were performed, and comparisons were made between the two models based on the predicted stress distribution of the reconstructed lumbar spine model, bone-growth area of the endplate, and the range of motion under various normal daily activities. Results: The load from the upper vertebral body was found to be effectively transmitted onto the lower vertebral body by a vertebral implant with the lateral fixation system; this was favorable for bone growth after surgery. However, significantly high stresses were concentrated around the interaction region between the screws and bone, owing to the uneven lateral fixation structure; this may increase the risk of bone fractures and screw loosening in the long term. For the posterior fixation case, stably posterior fixation structure was favorable to maintain stability for the reconstructed lumbar spine. However, the load was mainly transmitted via the fixation rod rather than the vertebral implant, owing to the stress shielding effect. Therefore, the predicted strain on the endplate were insufficient for bone ingrowth under most of the spinal activates, which could cause bone loss and prosthesis loosening. Conclusions: In this study, the comparisons of the reconstructed lumbar spine system with lateral and posterior fixation strategies were conducted. The Pros and Cons of these two fixation strategies was deeply discussed and the associated clinical issues were provided. The results of this study will have a clear impact in understanding the biomechanics of the lumbar spine with different fixation strategies and providing necessary instructions to the design and application of the lumbar spinal fixation system.